2+6(x-4)=3-18+3x

Simple and best practice solution for 2+6(x-4)=3-18+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2+6(x-4)=3-18+3x equation:


Simplifying
2 + 6(x + -4) = 3 + -18 + 3x

Reorder the terms:
2 + 6(-4 + x) = 3 + -18 + 3x
2 + (-4 * 6 + x * 6) = 3 + -18 + 3x
2 + (-24 + 6x) = 3 + -18 + 3x

Combine like terms: 2 + -24 = -22
-22 + 6x = 3 + -18 + 3x

Combine like terms: 3 + -18 = -15
-22 + 6x = -15 + 3x

Solving
-22 + 6x = -15 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-22 + 6x + -3x = -15 + 3x + -3x

Combine like terms: 6x + -3x = 3x
-22 + 3x = -15 + 3x + -3x

Combine like terms: 3x + -3x = 0
-22 + 3x = -15 + 0
-22 + 3x = -15

Add '22' to each side of the equation.
-22 + 22 + 3x = -15 + 22

Combine like terms: -22 + 22 = 0
0 + 3x = -15 + 22
3x = -15 + 22

Combine like terms: -15 + 22 = 7
3x = 7

Divide each side by '3'.
x = 2.333333333

Simplifying
x = 2.333333333

See similar equations:

| 5(v-8)-(v-2)=-22 | | 34=5x+6[-2x+15] | | 2x-84=11 | | y*6=7.2 | | 5=-5(6+v)+5(5v-1) | | 1/2(6x-8)-3=4(x-10) | | -7(1+3b)-6(2b-5)=56 | | K^2-3k-70= | | 5x+2.7=8.7 | | y=x^2+16x | | a^2-44-7a=0 | | ln(x+5)=.69x^2 | | -10+log[3](x+3)=-10 | | 40=-5(n-7)+5(1+n) | | log(x+5)=.69x^2 | | -4x-2[-3x-3]=-8 | | 11q+5p-9p+7q= | | 8x-29=180 | | 2x+2[2x+16]=98 | | -3x+18-6x=20 | | 5x+4-2x=-(x+80)+12 | | -7(6n-2)-(1+8n)=-37 | | 1/2(2x-4)2 | | 14m^2-10m=0 | | 24=6m+12 | | 1A=bh | | 95=2x+7[-x+20] | | -2p-8+p+3=0 | | 5(2x-8)+8(5x+6)=8 | | 2x+14+3x-2=180 | | 15x+10=-20 | | 6(r-1)+6(r-4)=-54 |

Equations solver categories